Kesesuaian Istilah Tindakan Medis Berdasarkan ICD-9-CM Pada Dokumen Rekam Medis Rawat Inap Non-PBI Triwulan I Di Rumah Sakit Umum Pusat Hasan Sadikin Tahun 2015 - Fahri Ramdan Hariri; Ida Wahyuni (STIKes Persada Husada Indonesia, 2015)
The Regulation of the Minister of Health of the Republic of Indonesia Number 27 Year 2014 on theIndonesian Systems Case Base Groups (INA-CBGS) Technical Guidelines that charging medical action terms,and action code refers to ICD-9cm. Based on preliminary studies in dr. Hasan Sadikin Central GeneralHospital, coders have difficulty in determining leadterm to define actions based on ICD-9-CM, giving rise to theassumption that resulted in inaccurate code determination. The study was conducted to determine the percentagelevel of medical procedures term conformity based on ICD -9-CM. This study is a descriptive study that seeks tolook back by re-reviewing or review back the use of the medical action term on NON-PBI inpatient medicalrecord document in the first quarter of 2015. Data obtained through observation using observation sheet andinterviews as supportive descriptives. The results showed that the use of medical action term is largely inaccordance ICD-9-CM with the corresponding percentage at 78% and in non-accordance of 22%. However, inorder to homogenize the perceptionof the medical action term usage, efforts should be made to address theimpact caused, by further enhancing the cooperation that has existed between physicians, nurses and otherhealthcare practitioners with medical records clerk about writing medical term measures appropriately basedon ICD- 9-CM.Keywords: Suitability, medical action term, ICD-9-CM.